Genome-wide identification and development of SSR molecular markers for genetic diversity studies in Ilex asprella - Li, Jingchun; Quan, Changqian; Wei, Rongchang; Wei, Fan; Ma, Qing; Huang, Yuquan; Xu, Meihua; Tang, Danfeng (Frontiers in Plant Science, 2025)
IntroductionIlex asprella is a common Chinese herb widely distributed in South China with high medicinal value, and its genetic diversity assessment is a prerequisite for the utilization of germplasm resources.MethodsBased on the published genome of I. asprella, this study conducted genome-wide SSR identification and development and performed genetic diversity analysis on 25 germplasm accessions.Results and discussionThe results showed that a total of 137,443 SSR loci were detected across the whole genome of I. asprella. Six types of SSRs were obtained, and the dinucleotide and trinucleotide repeats were dominant, with dinucleotide repeat motifs accounting for 84.20% of the total markers and trinucleotide repeat motifs accounting for 12.22%. A total of 15 highly polymorphic primers were ultimately selected, including 13 dinucleotide primers and 2 trinucleotide primers. The allele distribution of SSR loci in the genome of Ilex asprella was uneven, and the heterozygosity of different loci varied; the fixation index (F) were all greater than 0, indicating that there was an excess of pure heterozygotes in this population; the genetic differentiation coefficient (Fst) was 0.192, and there existed a large amount of genetic differentiation; the mean value of gene flow (Nm) between different loci was 1.175, and there existed a certain degree of gene exchange in the population; the molecular analysis of variance (AMOVA) indicated that the variation of individuals was the main source of total variation. Genetic analysis revealed that the 25 samples can be divided into three populations. pop2 had the highest genetic diversity, followed by pop3, and pop1 had the lowest genetic diversity, suggesting that there were differences in the level of genetic diversity among the populations. Overall, we found that there was a large genetic differentiation in the Ilex asprella population, a high level of genetic diversity, gene exchange between different populations, and high inter-population gene mobility, which was of guiding significance for the subsequent selection and breeding of new varieties of Ilex asprella.